2010
DOI: 10.1073/pnas.1008247107
|View full text |Cite
|
Sign up to set email alerts
|

Human RORγt + T H 17 cells preferentially differentiate from naive FOXP3 + Treg in the presence of lineage-specific polarizing factors

Abstract: RORγt + T H 17 cells are a proinflammatory CD4 + T-cell population associated with autoimmune tissue injury. In mice, priming of T H 17 requires TGF-β, which alone directs the priming of FOXP3 + regulatory T cells (Treg), in association with inflammatory cytokines. Priming of human T H 17 cells from conventional naive CD4 + T cells under similar conditions, however, has proved difficult to achieve. Here, we report that differentiation of human T H 17 cells preferentially occurs from FOXP3 + naive Treg (NTreg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
119
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(130 citation statements)
references
References 50 publications
(74 reference statements)
10
119
0
1
Order By: Relevance
“…23,[45][46][47] Although most of these studies indicated that human Foxp3 þ IL-17 þ cells retain regulatory capacity as long as they express Foxp3, it was suggested that they can foster the expression of proinflammatory cytokines and thus behave as ''inflammatory'' Tregs. 23 In addition, in vitro studies showed that human RORgt þ Th17 cells preferentially differentiate from naïve Foxp3 þ T cells that lose their Foxp3 expression 48 that may eventually lead to conversion into pathogenic Th17 cells under inflammatory conditions. 49 Additional studies in mice have shown that Foxp3 þ RORgt þ T cells have a regulatory function during autoimmune diabetes; 50 nevertheless, it was proposed that these cells represent intermediates that can differentiate either toward Foxp3 þ RORgt À Tregs or RORgt þ Foxp3 À Th17 cells.…”
Section: Discussionmentioning
confidence: 99%
“…23,[45][46][47] Although most of these studies indicated that human Foxp3 þ IL-17 þ cells retain regulatory capacity as long as they express Foxp3, it was suggested that they can foster the expression of proinflammatory cytokines and thus behave as ''inflammatory'' Tregs. 23 In addition, in vitro studies showed that human RORgt þ Th17 cells preferentially differentiate from naïve Foxp3 þ T cells that lose their Foxp3 expression 48 that may eventually lead to conversion into pathogenic Th17 cells under inflammatory conditions. 49 Additional studies in mice have shown that Foxp3 þ RORgt þ T cells have a regulatory function during autoimmune diabetes; 50 nevertheless, it was proposed that these cells represent intermediates that can differentiate either toward Foxp3 þ RORgt À Tregs or RORgt þ Foxp3 À Th17 cells.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that, after stimulation in the presence of Th17-polarizing cytokines, human Th17 preferentially differentiate from NnTreg rather than from conventional naive CD4 + T cells (12 Fig. 6, induction of IL-1RI expression was an early event of Th17 cell differentiation from NnTreg, as it was detected in a significant fraction of the cells early after stimulation, before cell division.…”
Section: Il-1ri Expression Identifies CM Foxp3mentioning
confidence: 99%
“…In addition, MTreg contain a hybrid subpopulation of cells coexpressing FOXP3 and RORgt that exert suppressive functions but concomitantly secrete IL-17 ex vivo (9,10). Finally, in the presence of IL-1, IL-2, TGF-b, and IL-23, human Th17 cells preferentially differentiate from natural naive regulatory T cells (NnTreg), a population of thymically derived human regulatory T cell (Treg) precursors (11), rather than from conventional CD4 + CD25 2 naive T cells (12). Together, these data suggest that the differentiation pathway of Treg and Th17 cells is partially common.…”
Section: D4mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that FOXP3-expressing Tregs can be divided into two distinct subsets: naturally occurring Tregs (nTregs), and peripherally induced Tregs (iTregs), which differentiate under tolerogenic conditions in peripheral lymphoid tissues (4,5). FOXP3-expressing nTregs develop in the thymus via central tolerance mechanisms and, upon egress, they express the naive T cell marker CD45RA until they encounter their cognate Ag and become activated in the periphery (6,7). Their TCR repertoire is diverse but thought to be largely restricted to self-Ags (8).…”
Section: T Regulatory Cells (Tregs) Play a Critical Role In Establishingmentioning
confidence: 99%